Secondary two express mathematics examination papers (Singapore : Educational Publishing House, 2014)
Mathematics Examination Papers is specially written according to the latest guidelines issued by the Ministry of Education. It provides a comprehensive coverage of the topics taught in the Express stream. It comprises 8 sets of examination practice papers to familiarise students with the types of questions commonly set in the examinations. Each set of examination practice paper contains Paper 1 and Paper 2. Students will gain confidence and do well in their examinations and tests after working through all questions in this book. Full worked solutions are provided to facilitate self-checking or marking.
Keywords: Mathematics--Examinations--Periodicals.